2022
DOI: 10.3390/diagnostics12112686
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Pyogenic Spondylitis Caused by S. constellatus: A Case Report

Abstract: Streptococcus constellatus (SC) is a species of Streptococcus belonging to the Streptococcus anginosus group, along with Streptococcus anginosus and Streptococcus intermedius. Despite its commensal nature, underlying risk factors and medical conditions might lead to various anatomic site infections caused by this opportunistic pathogen. Although SC infections have mostly been associated with bacteremia, some case reports of abscess and empyema formation have been documented. Herein, we report a case of a middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Streptococcus constellatus is an extremely rare SEA pathogen with only a few cases. For instance, Dai et al reported that a 58-year-old female had SEA caused by Streptococcus constellatus infection, 7 Korugan et al reported invasive suppurative spondylitis caused by Streptococcus constellatus infection, 8 Jin et al reported another obese patient with acute suppurative spondylitis caused by Streptococcus constellatus , 3 and Takada et al reported a rare case of suppurative thrombophlebitis of the posterior neck caused by Streptococcus constellatus . 9 All of these patients recovered after surgery and 6–8 weeks of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus constellatus is an extremely rare SEA pathogen with only a few cases. For instance, Dai et al reported that a 58-year-old female had SEA caused by Streptococcus constellatus infection, 7 Korugan et al reported invasive suppurative spondylitis caused by Streptococcus constellatus infection, 8 Jin et al reported another obese patient with acute suppurative spondylitis caused by Streptococcus constellatus , 3 and Takada et al reported a rare case of suppurative thrombophlebitis of the posterior neck caused by Streptococcus constellatus . 9 All of these patients recovered after surgery and 6–8 weeks of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus constellatus (SC) is a part of Streptococcus anginosus group and is usually colonized in the normal mouth, gut, and urogenital tract flora. [ 1 ] However, in some specific cases, it has the potential to spread to physiologically sterile anatomical sites and cause infections. According to its anatomical distribution, SC can cause suppurative infections at multiple anatomical sites, mostly in patients who are immunosuppressed or undergoing invasive procedures.…”
Section: Introductionmentioning
confidence: 99%